ĐÁNH GIÁ HIỆU QUẢ ĐỊNH DANH CÁC CHỦNG Burkholderia pseudomallei KHÔNG ĐIỂN HÌNH BẰNG VITEK 2 - Zakharova , I. B.; Bùi, Thị Lan Anh; Teteryatnikova, N. N.; Chirskov, P. R. (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ASSESSMENT ON THE EFFECTIVENESS OF DETERMINING ATYPICAL BURKHOLDERIA PSEUDOMALLEI STRAINS BY VITEK 2 SYSTEMThe rate of accurate identification of B. pseudomallei strains causing melioidosis is about 86% by the Vitek 2 system. For atypical strains, sensitive to gentamicin, this rate is only about 57%. The mistaken identification of the causative agent lead to incorrect treatment regimens, which can lead to die. 30 strains of B. pseudomallei isolated from clinical samples, 6 strains of B. pseudomallei and 6 strains of B. thailandensis isolated from soil samples were identified using Vitek 2 system. The above bacterial strains were confirmed by multiplex PCR method and gene sequencing in previous studies. The results indicated that by Vitek 2 system, B. pseudomallei strains isolated from clinical samples had an accuracy rate of 97 %, B. pseudomallei strains isolated from soil samples had an accuracy rate of only 67%. Thus, the Vitek 2 identification method gives high diagnostic efficiency on typical B. pseudomallei strains isolated from clinical samples. However, with the group of bacteria B. pseudomallei atypical, isolated from soil, the wrong detection results up to 75%. The malonate reaction (MNT) on Vitek 2 is considered an important marker to distinguish B. thailandensis from B. pseudomallei.